En los estudios, en las ondas y en el hogar: la relación entre las mujeres y Radio Nacional de España durante el franquismo desarrollista (1960-1975) - José Emilio Pérez Martínez (Cahiers de Civilisation Espagnole Contemporaine)
For a long time, historiography has barely paid attention to the role that women have played within the radio. This paper aims to analyse the ways in which Spanish women interacted with Radio Nacional de España during the 1960s and 1970s. In order to do so, we will consider realities such as the workers of the radio station, the women's programmes and their discourses of femininity and their consumption by the audience. In this way we will try to reach a global understanding of this relationship, to improve our understanding of the way in which gender ideology was produced during the dictatorship.